Socialize the Ilahiyah Doctrine on Corporate Social Responsibility in the Modern Business - Zakiy, Faris Shalahuddin; Ramadhan, Dwi Swasana (The Pontianak State Institute of Islamic Studies, 2019)
This research aims to explore the theoretical framework that underlies how and why companies must take social perspectives in Islam. The importance of this study is to position the facts that seek to find a connection between the theoretical framework and the practice of social responsibility. This study used a qualitative approach, namely the study of literature. The practice of social responsibility will be analyzed based on legal aspects, muttafaq, mukhtalaf, history and other sources that relevant to this research. This research shows that the Indonesian law and the underlying Islamic theory support companies to implement CSR. Although disclosure in Indonesia is still voluntary, companies will get benefit to increasing the transparency, accountability, communication, improving business strategies such as financial rewards, competing challenges, global practice, good image, investor attractiveness, appreciation and recognition and ready for the regulation.